KOMPOSISI LIMBAH IKAN DALAM PAKAN TERHADAP KANDUNGAN PROTEIN IKAN PATIN (Pangasius hypophthalmus HB) - Rimalia, Anny (Fakultas Pertanian UVAYA Banjarmasin, 2021)
The aim of the study was to determine the protein content of catfish fed with feed from fish waste with different compositions. Fish waste, consisting of entrails, fish heads, scales, and shrimp shells. The content of the waste contains 29.70% protein, 18.83% fat, 1.94% carbohydrates, 8.97 water content. This study used a completely randomized design (CRD) consisting of four treatments and replications. The factors consist of (A) 70% fish waste, (B) 50% fish waste, (C) 30% fish waste (D) pellet comfeed feed. Results The protein content of catfish at the beginning of the observation was 12.75%, and at the end of the treatment study (A) 8.20%, (B) 15.77%, (C) 12.84%, D (15.54%), Results the protein content was relatively good in treatment (B), but overall that the protein content for all treatments was still within the normal range.